Metabolic coupling in urothelial bladder cancer compartments and its correlation to tumor aggressiveness - Afonso, Julieta (2016)
Monocarboxylate transporters (MCTs) are vital for intracellular pH homeostasis by extruding lactate from highly glycolytic cells. These molecules are key players of the metabolic reprogramming of cancer cells, and evidence indicates a potential contribution in urothelial bladder cancer (UBC) aggressiveness and chemoresistance. However, the specific role of MCTs in the metabolic compartmentalization within bladder tumors, namely their preponderance on the tumor stroma, remains to be elucidated. Thus, we evaluated the immunoexpression of MCTs in the different compartments of UBC tissue samples (n = 111), assessing the correlations among them and with the clinical and prognostic parameters. A significant decrease in positivity for MCT1 and MCT4 occurred from normoxic toward hypoxic regions. Significant associations were found between the expression of MCT4 in hypoxic tumor cells and in the tumor stroma. MCT1 staining in normoxic tumor areas, and MCT4 staining in hypoxic regions, in the tumor stroma and in the blood vessels were significantly associated with UBC aggressiveness. MCT4 concomitant positivity in hypoxic tumor cells and in the tumor stroma, as well as positivity in each of these regions concomitant with MCT1 positivity in normoxic tumor cells, was significantly associated with an unfavourable clinicopathological profile, and predicted lower overall survival rates among patients receiving platinum-based chemotherapy. Our results point to the existence of a multi-compartment metabolic model in UBC, providing evidence of a metabolic coupling between catabolic stromal and cancer cells' compartments, and the anabolic cancer cells. It is urgent to further explore the involvement of this metabolic coupling in UBC progression and chemoresistance.